Malaysian Consumers’ Intention To Adopt A Smart Speaker In Home Appliances - Zalman, Puteri Nurafiqah Wahida Wan Mohammad (2022)
The adoption of smart speakers in many countries has increased significantly over the years, however, the adoption rate in Malaysia is still quite low. This study provides insights into the Malaysian consumers’ attitude towards intention to adopt smart speakers and evaluates the adoption intention’s impact as the mediator in the relationship between factors and intention to adopt. This empirical study is based on an online questionnaire using a sample of 200 Malaysian consumers. The relationship between the independent variables (perceived usefulness, perceived ease of use, security and price), the mediator (attitude) and the dependent variable (intention to adopt) were examined using regression analysis, Baron and Kenny’s (1986) tests of mediation, and others. This study also examined if gender and age moderate attitude. The result reveals that attitude plays an important role as it mediates the relationship between the factors and intention to adopt. Factors such as PU, PEOU, security and price are all important factors especially to the Malaysian consumer as this influences their attitude to adopt smart speakers. This study has extended the literature in linking the relationship between attitude, factors and intention to adopt. This study took place during the COVID19 pandemic where many people worked from home or had lost their jobs. This could cause many participants to see smart speakers as expensive and not a necessity which could affect the results.